The ANALISIS STUDI KELAYAKAN BISNIS PADA USAHA TAHU SUSU LEMBANG DARI ASPEK PRODUKSI DAN ASPEK PEMASARAN: Analisis Kelayakan Bisnis Pada Produk Tahu Susu Lembang - Muhammad Irfan; Ramayani Yusuf; Dyah Bayu Pramesthi (Jurnal Ekonomi Manajemen Bisnis Dan Akuntansi : EMBA, 2026)
The analysis of a business feasibility study is an important initial step in starting a business and assessing its viability. This research focuses on the production and marketing aspects of Tahu Susu Lembang. The study uses a descriptive qualitative research method with primary data and direct observation. Tahu Susu Lembang is one of the typical souvenirs of Lembang. The production process of Tahu Susu Lembang has attracted significant attention because it uses high-quality ingredients. From a marketing perspective, the unique drive-thru facility also serves as an effective marketing strategy to serve customers. Tahu Susu Lembang has the potential to be further developed by paying attention to raw material standards, production processes, and effective marketing strategies to make it one of the attractive culinary tourism destinations in Lembang